„Indywidualistyczne” vs „kolektywistyczne” orientacje normatywne młodzieży akademickiej - Cybal-Michalska, Agnieszka (Studia Edukacyjne, 2017)
In the article, the author refers to the individualism-collectivism dichotomy, which is a theoretical construct serving to explain the mutual relations of the individual and the group. It moreover provides a dimension differentiating between cultures which give the primacy to the individual over the group and those, which privilege the group over the individual. An individualistic tendency means that an individual is the subject for whom the collective is an object of action. Collectivism is the polar opposite view: the collective entity is the proper subject of the proceedings, in relation to which individuals are objects. The author of the article, acknowledging the need to recognize the quality of images and views of academic youth about a career path, invoked the structure and function of selected normative assumptions as important dimensions of the socio-cultural mentality of the individual. The research study helped grasp the ‘individualistic’ and ‘collectivist’ normative assumptions of university youth,, emerging in the course of socialization and originating in the generalization of social experience.